Association between thyroid autoimmunity and antinuclear antibody prevalence among pregnant women: a cross-sectional study in Qingdao, China - Wu, Mingran; Wan, Yanzhen; Zhao, Lin; Kang, Shan; Hao, Guiliang; Guo, Mingzhen; Wang, Shuai; Dong, Jianhong; Song, Jinlian (Frontiers in Endocrinology, 2024)
Objective: To identify the relationship between thyroid autoimmunity and antinuclear antibody (ANA) prevalence in Chinese pregnant women. Methods: The study involved 1923 first-trimester women who were measured for thyroid stimulating hormone (TSH) level, thyroid autoantibodies (thyroperoxidase antibody [TPOAb] and thyroglobulin antibody [TgAb]) and ANA titer. Social demographic data were collected through standardized questionnaires. Results: In this study, 23.3% of pregnant women tested positive for TPOAb and 9.9% tested positive for TgAb. Women with a positive ANA were more likely to be TPOAb-positive or TgAb-positive than women with a negative ANA (adjusted odds ratio [AOR] 1.96, 95% confidence interval [CI] 1.47-2.62 for TPOAb [+]; AOR 3.12, 95% CI 2.18-4.48 for TgAb[+]). In addition, ANA titers were closely associated with thyroid autoimmunity. Women with an ANA titer of ＞1:320 had a significant higher risk of being TPOAb positive or TgAb positive (AOR 4.49, 95% CI 1.48-13.66 for TPOAb [+]; AOR 5.51, 95% CI 1.65-18.49 for TgAb [+]). The higher the ANA titer, the greater the risk of developing thyroid autoimmunity, especially for those with a high ANA titer. Conclusions: ANA positivity is strongly correlated with thyroid autoimmunity. Further study is warranted to clarify the causal relationship between thyroid autoimmunity and ANA in pregnant women.This research is essential to evaluate and predict the risk of co-existing autoimmune disorders,leading to improved care for pregnancy and neonatal health.